Mesogenic Properties of a Series of Synthesized Calamitic Liquid Crystals Containing 1,2,4,5-Tetrazine Moieties - Abdul Halim, Noor Hafizah (2009)
In this research, a series of calamitic liquid crystal containing 1,2,4,5-tetrazine moieties have been synthesized. 1,2,4,5-tetrazine is a mesomorphic compound containing heterocyclic units and such structures have greater possibilities to obtain mesogenic molecules. All compounds were synthesized by esterication of HOC6H4C2N4C6H4OH with carboxylic acids that vary in substituents chain lengths. The structures of the liquid crystal compounds were elucidated based on FT-IR, mass spectroscopy, CHN and NMR analyses. The infrared spectra of the compounds showed the characteristic of the tetrazine and ester functional group for νC=O, νC=C, νC=N, νN-N and νC-O at (1750-1758 cm-1), (1602-1604 cm-1), (1318-1396 cm-1), (1142-1168 cm-1) and (1016-1102 cm-1). The elemental analyses agree with the expected formula R-C6H4C2N4C6H4-R where R = C2H5 (FZ-4), C4H9(Isobutyl) (FZ-49E), C5H11 (FZ-37B), C11H23 (FZ-53), C15H31 (FZ-34A) and C17H35 (FZ-35A). The 1H NMR spectra reflected the high symmetry of the molecules with the benzene protons appeared as a doublet at δ(8.69–8.67ppm) and δ(7.36-7.34ppm), respectively. The 13C signals for the 1,2,4,5-tetrazine, C=O and C-O appeared at δ(163.30-163.25), δ(171.82-171.02ppm) and δ(154.48-154.40ppm), respectively. Differential scanning calorimetry (DSC) and polarizing optical microscopy (POM) analyses of FZ-37B, FZ-53, FZ-34A and FZ-35A revealed the existence of smectic and schlieren smectic mesophases.